The road to somewhere the new tribes shaping British politics - Goodhart, David (UK Penguin Books, 2017)
Many Remainers reported waking up the day after the Brexit vote feeling as if they were living in a foreign country. In fact, they were merely experiencing the same feeling that many British people have felt every day for years.
Includes bibliographical references and index
Keywords: Populism